Bryophytes in conservation units: A scientometric analysis (Research, Society and Development, 2021)
Conservation Units (CUs) are territorial spaces instituted by the government that have the purpose of conserving relevant natural characteristics. The Bryophytes, which in addition to constituting the flora of these areas, are more vulnerable to loss of environments than other terrestrial plants, in addition to this the fact that there is no collection of living material, and thus, can only be conserved by the preservation of natural areas. The objective was collect data on work with Bryophytes in CUs to complete the group's knowledge in protected areas, and also to detect possible lack of studies in different areas of Brazil. In the Web of Science ™ database, a search was performed using the descriptors, combined with the boolean operator AND arranged as follows: bryophytes AND protected area, bryophytes AND unit conservation, bryophytes AND national park, bryophytes AND state park. There were 119 articles published for different countries between the years 2010 to 2020. A large number of articles were concentrated in the years 2014 and 2016. England is the country that publishes the most on the topic and Brazil occupies second place. The search obtained the majority of the results concentrated in the ​​Plant Science (35%), and Environmental Science (28%), among these, the areas most related to the topic addressed. This study draws attention to some gaps regarding the knowledge of bryophytes in CUs, highlighting the need for research with this plant group in some regions of Brazil, where several states in the Northeastern continue to be undersampled in relation to bryophyte. And reinforce the importance of choosing indexed journals in relevant databases, for greater visualization of researches.